Empowering Future English Teachers: Innovative Strategies for Cultivating Communicative Competence - Rahmonova Charos Farrukh qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
In an era marked by rapid globalization and intercultural interaction, the role of effective communication in language education has never been more critical. This thesis explores the methods of developing communicative competence among future English teachers, addressing not only the theoretical underpinnings of this concept but also practical strategies that can be implemented in teacher training programs. By synthesizing contemporary research and pedagogical practices, this work aims to highlight the importance of equipping future educators with the skills necessary to facilitate meaningful language use in diverse contexts.